2014
DOI: 10.1002/alr.21376
|View full text |Cite
|
Sign up to set email alerts
|

Hemostatic effect of hot saline irrigation during functional endoscopic sinus surgery: a randomized controlled trial

Abstract: HSI may be beneficial in improving surgical field of view in FESS after 2 hours of operating time. A significant reduction in rate of blood loss may be attained with HSI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
103
0
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(108 citation statements)
references
References 23 publications
2
103
0
3
Order By: Relevance
“…Furthermore, Ozmen et al found in a randomized controlled trial of 120 children that 500C saline solution was substantially better than room-temperature saline to obtain postadenoidectomy hemostasis (7) . This is in accordance with findings from two studies showing that hot saline irrigation during functional endoscopic sinus surgery reduced blood loss compared to irrigation with room temperature saline (8,9) . Despite, the promising results from Novoa et al, there is still limited use of water irrigation in clinical practice.…”
Section: Introductionsupporting
confidence: 92%
See 1 more Smart Citation
“…Furthermore, Ozmen et al found in a randomized controlled trial of 120 children that 500C saline solution was substantially better than room-temperature saline to obtain postadenoidectomy hemostasis (7) . This is in accordance with findings from two studies showing that hot saline irrigation during functional endoscopic sinus surgery reduced blood loss compared to irrigation with room temperature saline (8,9) . Despite, the promising results from Novoa et al, there is still limited use of water irrigation in clinical practice.…”
Section: Introductionsupporting
confidence: 92%
“…The suggested threshold temperature of 520C for mucosal tissue necrosis was derived from an experimental study in rabbits (10) . More recent human studies on hot water irrigation, have all used water temperatures of 500C or less and tissue necrosis has not been reported (6,7,(11)(12)(13)(14)(15) . Specifically, in the study from Schlegel-Wagner et al patients were examined between 4 and 24 months after 500C hot water irrigation for epistaxis without signs of mucosal injury (12) .…”
Section: Discussionmentioning
confidence: 99%
“…Saline delivered at a temperature of 49 C demonstrated a beneficial impact on surgical field for cases lasting longer than 2 hours. 31 The types of anesthetic and degree of hemodynamic control have also been suggested to influence intraoperative blood loss and visualization. Several studies have suggested that total intravenous anesthesia reduces peripheral vasodilation and improves the quality of the surgical field, whereas other reports have found no improvement; therefore, further investigation is warranted.…”
Section: Intraoperative Phasementioning
confidence: 99%
“…Multiple methods have been described to improve visualization and decrease bleeding including use of total intravenous anesthesia [6,7], local infiltration with epinephrine [11], topical decongestants [12], head of bed elevation [5], warm water irrigation [13], greater palatine canal injection with epinephrine [14], and preoperative oral steroid therapy [4]. Recent data demonstrating the safety of concentrated topical epinephrine indicates that it is safe, minimizes blood loss and potentially obviates the need for oral steroid use [8].…”
Section: Discussionmentioning
confidence: 99%